The Credit Crunch : How the Use of Movable Collateral and Credit Reporting Can Help Finance Inclusive Economic Growth in Nigeria - Central Bank of Nigeria; International Finance Corporation (International Finance Corporation, Washington, DC, 2017)
Nigeria is an entrepreneurial economy with an estimated thirty seven million Micro, Small, and Medium-sized Enterprises (MSME) in the country, and their contribution to economic growth and job creation is significant. There are also a large number of self-employed entrepreneurs who support themselves and their families by supplying goods and services to the economy. Many of these businesses have the potential to become bigger and more prosperous, but their growth is restricted for a variety of reasons. Access to finance has been singled out as a crucial prerequisite to the growth of these businesses. This report identified collateral as the missing link between the small-scale business sector and the financial institutions that could provide the necessary capital for them to grow. This means formal lending is virtually inaccessible for these small businesses and entrepreneurs, who instead rely on informal, unregulated, and unpredictable credit in order to expand their operations. To improve access to finance and promote inclusive economic growth, the Central Bank of Nigeria (CBN), in partnership with the International Finance Corporation (IFC), a member of the World Bank Group and the largest global development institution focused on the private sector in emerging markets, has established the National Collateral Registry and is supporting the development of a modern credit reporting system in Nigeria. This new financial infrastructure will allow for increased use of moveable and reputational collateral to make it possible for more MSMEs to access financing through the formal sector.